Meningkatkan Kemampuan Siswa Menulis Teks Recount Bahasa Inggris Menggunakan Three Phases Techniques pada Kelas VIII.1 (Bilingual) SMP Negeri 7 Mataram - Suherni, Suherni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
This study aims to improve students' ability to produce Recount text through personalization by Three Phases Techniques method. This research uses classroom action research method. This PTK is conducted within 3 (three) cycles in which each cycle lasts for 3 meetings, and each meeting takes 2 x 45 minutes. Evaluation results in each cycle show significant progress. In the first cycle, the average score reached 77.60 students with the percentage of completeness reached 81.39%, based on 75K Maximum Criterion (KKM) 75.00. In the second cycle, the average value of students increased to 79.90% with the percentage of completeness reached 83.72%. Because the percentage of mastery has not reached the classical completeness requirement (85%), then proceed with the third cycle. Results of the third cycle showed that the average value of students increased to 83.80% and the percentage of completeness reached 95.30%. This indicates that in this cycle there has been a classical completeness in which the minimum standard is 85%. Thus it can be said that by using Three phases techniques is suitable to be applied in learning Recount text